Acute and chronic neural stimulation via mechano-sensitive ion channels - Tay, Andy Kah Ping (Springer theses recognizing outstanding Ph.D. Research, 2018)
This book describes the tools, developed by the author, for perturbing endogenous mechano-sensitive ion channels for magneto-mechanical neuro-modulation. He explores the ways in which these tools compare against existing ones such as electricity, chemicals, optogenetics, and techniques like thermos/magneto-genetics. The author also reports on two platforms-magnetic ratcheting and magnetic microfluidics for directed evolution and high throughput culture of magnetotactic bacteria-that produce high quality magnetic nanoparticles for biomedical applications like neural stimulations. This thesis was submitted to and approved by the University of California, Los Angeles.